Analisis Penggunaan Bahasa Indonesia dalam Dakwah Ustad Hanan Attaki - Bintang Astian Hamzah; Muhamad Faizudin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Indonesian has an important position and function for the Indonesian nation in the territory of the Unitary State of the Republic of Indonesia (NKRI). Indonesian has become the national language since the agreement was stipulated in the Youth Pledge on October 28 1928, functioning as a symbol of pride, a symbol of identity, a means of unification and a means of communication. The position and function of Indonesian in religion, namely as a link between spoken and written languages, was emphasized by the Islamic religious figure